2017
DOI: 10.1016/j.apsoil.2017.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of soil biosolarization with mesophilic and thermophilic solid digestates on soil microbial quantity and diversity

Abstract: Soil biosolarization (SBS) is a pest control technique that combines passive solar heating and fermentation of amended organic matter. The extreme soil conditions generated during SBS could decrease microbial biomass and restructure the soil microbiome, which could impact soil quality. Digestates from anaerobic digesters may harbor microbial communities tolerant of the oxygen, moisture, and temperature stresses encountered during SBS as these conditions may also occur in digesters.Digestate microbial communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Amendment addition positively affected the OM and K content after the solarization process, as observed in prior studies . In addition to these specific impacts, other studies also observed that organic amendments followed by solarization led to higher values of total N, total P, several enzyme activities, microbial biomass C, potentially mineralizable N, water‐soluble organic C and microbial functional diversity when compared with non‐amended soils . Biosolarization studies using thermophilic and mesophilic digestates showed a significant decrease in EC after solarization .…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Amendment addition positively affected the OM and K content after the solarization process, as observed in prior studies . In addition to these specific impacts, other studies also observed that organic amendments followed by solarization led to higher values of total N, total P, several enzyme activities, microbial biomass C, potentially mineralizable N, water‐soluble organic C and microbial functional diversity when compared with non‐amended soils . Biosolarization studies using thermophilic and mesophilic digestates showed a significant decrease in EC after solarization .…”
Section: Discussionmentioning
confidence: 54%
“…In addition, it has been observed that native microbial communities in the soil contribute to the suppression of Fusarium spp. 44 As SBS has been shown to have a significant impact on the soil microbial community, 45 future studies are needed to determine how SBS-induced changes to the soil microbiota affect long-term FOL suppression. Amendment addition positively affected the OM and K content after the solarization process, as observed in prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the presence of Firmicutes and Proteobacteria in biosolarization systems (Fernandez‐Bayo et al . ) and in GW and municipal solid waste composts (Vaz‐Moreira et al . ; Pankhurst et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, the same treatment using 1Á5 wt% mesophilic digestate did not significantly increase B. nigra mortality compared to the control treatments (Fernandez-Bayo et al 2017b). It is possible that differences in performance were due in part to compositional differences in the amended substrate and micro-organisms involved in the biotransformation of substrates to biopesticidal compounds (Fernandez-Bayo et al 2017a).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation